Evaluation of Leadership Programs (PIM) Level III For Civil Servants In The Education and Training Center (Pusdiklat) of The Ministry of Manpower (Kemnaker) RI - Sudiharto; Dedi Purwana; Billy Tunas (Program Studi S3 Ilmu Manajemen, 2019)
The purpose of this study is to describe the implementation of Level III Education and Training Program (PIM III) for Civil Servants (PNS) in the Education and Training Center Institution of the Ministry of Manpower Republic of Indonesia (Pusdiklat Kemnaker RI), so that it can be used by policy makers to improve its implementation. The research method uses the program evaluation model CIPP (Context, Input, Process and Product) and Impact. Evaluation was carried out on the implementation of Program Diklat PIM III held in the 2015-2016 period by the Pusdiklat Kemnaker RI. In this study involved 57 informants from the Ministry of Administrative and Bureaucratic Reform (PAN RB) as regulators, the State Administration Institute (LAN) as the implementing policy, National Board for Placement and Protection of Indonesian Overseas Workers (BNP2TKI ) as a place for alumni and the Pusdiklat Kemnaker RI as the organizer. Overall the results of evaluation research on the implementation of the Program Diklat PIM III by the Pusdiklat Kemnaker RI is considered to be Less or 57.69% of the evaluation criteria can be met. The Context Sub-focus (C) reaches a value of Very Less or 40.43%; The Input subfocus achieved a Good value or 77.92%; The Process sub-focus (P) achieves Very Good or 100%; The Product sub-focus (P) achieves less or 59% and The Impact (I) of alumni on organizations reach Very Less or 11.1%. The recommendations of this study can be applied to the Program Diklat PIM III Cycle Model as part of the Echelon III Position Selection with the central point of the Echelon III Structural Position Competence set by the measured and traceable PANRB so as to produce superior and competitive human resources personnel.